Successful Utilization of Mechanical Thrombectomy in a Presentation of Pediatric Acute Ischemic Stroke - Esther S. Kim; Erica K. Mason; Andrew Koons; Shawn M. Quinn; Robert L. Williams (Case Reports in Pediatrics)
Guidelines regarding the management of acute ischemic stroke (AIS) in the pediatric population using mechanical recanalization procedures are lacking. We present a case of a 14-year-old male diagnosed in the Emergency Department with an acute onset stroke who underwent successful mechanical clot removal by interventional radiology.